Notice of Joint Meeting Between Camarillo and Oxnard Airport Authorities December 9, 1999, Appointment of Members to the Mission Statement Committee, and Five-Year Capital Improvement Plan - Rodney L. Murphy::::::; John K. Flynn:::::: (1999)
The agenda for a meeting on December 9, 1999 between the Camarillo Airport Authority and the Oxnard Airport Authority. Includes correspondence discussing the appointment of members to a mission statement committee for the Oxnard Airport, and correspondence discussing the Five-Year Capital Improvement Plan.